Ultraviolet curable resin composition, method for producing organic EL light-emitting device, and organic EL light-emitting device
By using an ultraviolet curable resin composition with a high boiling point acrylic compound and a photopolymerization initiator, a sealing material with high heat resistance and low gas release properties is formed, and the problem of moisture intrusion is solved, and the stability and light of the organic EL element are improved. Output efficiency.
Patent Information
- Application Number
- CN201980063298.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-27
- Filing Date
- 2019-08-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2039-08-30
AI Technical Summary
The prior art is difficult to effectively inhibit the invasion of moisture into organic EL elements, resulting in the generation and growth of dark spots, and even after covering with sealing materials, it is impossible to fully prevent moisture invasion.
The ultraviolet curable resin composition containing an acrylic compound having a boiling point of 270°C or above and a photopolymerization initiator is used to form a sealing material by inkjet method and curing with ultraviolet rays, ensuring high heat resistance and low gas release properties of the sealing material. This prevents moisture from invading.
Effectively prevent moisture invasion, the stability and life of organic EL components have been improved, the light transmittance of the sealing material has been improved, and the light output efficiency has also been improved.
Smart Images

Figure CN112753280B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an ultraviolet curable resin composition, a method for producing an organic EL light-emitting device, and an organic EL light-emitting device. Specifically, it relates to an ultraviolet curable resin composition for sealing an organic EL element, a method for producing an organic EL light-emitting device using the ultraviolet curable resin composition, and an organic EL light-emitting device having the sealing material. Background Art
[0002] Organic EL light-emitting devices are used for lighting, display, etc., and are expected to become more popular in the future.
[0003] Among organic EL light-emitting devices, a device called a top emission type is, for example, a device in which an organic EL element is arranged on a supporting substrate, a transparent substrate is arranged in a manner opposite to the supporting substrate, and a transparent sealing material is filled between the supporting substrate and the transparent substrate. In this case, light emitted by the organic EL element can be emitted to the outside through the sealing material and the transparent substrate.
[0004] The sealing material inhibits the intrusion of moisture into the organic EL element, thereby inhibiting the generation and growth of dark spots in the organic EL element. Dark spots are portions of the organic EL element that do not emit light due to moisture degradation.
[0005] The sealing material is made of a material containing an organic resin selected from epoxy resin or acrylic resin (see Patent Document 1). In particular, when acrylic resin is used, the sealing material can be made by curing the material by ultraviolet irradiation or the like, so that the sealing material can be made without applying a load caused by heat to the organic EL element.
[0006] Even when the organic EL element is covered with a sealing material, it may not be possible to sufficiently suppress the intrusion of moisture into the organic EL element.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 5581332 Summary of the invention
[0010] The present invention aims to provide a UV-curable resin composition that can be used to prepare a sealing material for sealing an organic EL element, which can prevent moisture from penetrating into the organic EL element, a method for manufacturing an organic EL light-emitting device using the UV-curable resin composition, and an organic EL light-emitting device having a sealing material containing a cured product of the UV-curable resin composition.
[0011] An ultraviolet curable resin composition according to one embodiment of the present invention is used for organic EL sealing and contains an acrylic compound (A) and a photopolymerization initiator (B). The acrylic compound (A) contains an acrylic compound (A1) having a structure represented by the following formula (1) and a boiling point of 270° C. or higher.
[0012] CH2=CR 1 -COO-(R 3 -O) n -CO-CR 2 =CH2…(1)
[0013] In formula (1), R 1 and R 2 are hydrogen or methyl, n is an integer greater than 1, R 3 is an alkylene group having 3 or more carbon atoms. When n is 2 or more, a plurality of R 3 They may be the same or different. The percentage of the acrylic compound (A1) relative to the acrylic compound (A) is 50% by mass or more. The acrylic compound (A) does not contain a compound having a boiling point of 260°C or less, or the proportion of compounds having a boiling point of 260°C or less in the acrylic compound (A) is 10% by mass or less.
[0014] A method for manufacturing an organic EL light-emitting device according to one embodiment of the present invention is a method for manufacturing an organic EL light-emitting device having an organic EL element and a sealing material covering the organic EL element, which comprises: molding the ultraviolet curable resin composition by an inkjet method, and then irradiating the ultraviolet curable resin composition with ultraviolet rays to cure it, thereby preparing the sealing material.
[0015] An organic EL light-emitting device according to one embodiment of the present invention includes an organic EL element and a sealing material covering the organic EL element, wherein the sealing material is a cured product of the ultraviolet curable resin composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic cross-sectional view showing a first example of an organic EL light-emitting device in one embodiment of the present invention.
[0017] Figure 2 This is a schematic cross-sectional view showing a second example of the organic EL light-emitting device in one embodiment of the present invention. DETAILED DESCRIPTION
[0018] Hereinafter, one embodiment of the present invention will be described.
[0019] The ultraviolet curable resin composition for sealing an organic EL element of the present embodiment (hereinafter also referred to as composition (X)) contains an acrylic compound (A) and a photopolymerization initiator (B). The acrylic compound (A) contains an acrylic compound (A1) having a structure represented by the following formula (1) and a boiling point of 270° C. or higher.
[0020] CH2=CR 1 -COO-(R 3 -O) n -CO-CR 2 =CH2…(1)
[0021] In formula (1), R 1 and R 2 are hydrogen or methyl, n is an integer greater than 1, R 3 is an alkylene group having 3 or more carbon atoms. When n is 2 or more, a plurality of R 3 Can be the same or different.
[0022] The acrylic compound (A1) accounts for 50% by mass or more of the acrylic compound (A). The acrylic compound (A) does not contain a compound having a boiling point of 260° C. or less, or the proportion of the compound having a boiling point of 260° C. or less in the acrylic compound (A) is 10% by mass or less.
[0023] The sealing material 5 of the organic EL light-emitting device 1 can be prepared from the composition (X) (see Figure 1 ). Outgassing caused by the acrylic compound (A1) is not likely to occur from the sealing material 5. Therefore, it is not likely to generate gaps caused by outgassing in the organic EL light-emitting device 1. Therefore, it is not likely to cause moisture to intrude into the organic EL element through the gap. In addition, the acrylic compound (A1) is not likely to increase the affinity of the sealing material 5 with water, so it is not likely to cause moisture to intrude into the organic EL element through the sealing material 5. Therefore, it is not likely for moisture to intrude into the organic EL element.
[0024] The glass transition temperature of the cured product of the composition (X) is preferably 80°C or more. That is, the composition (X) preferably has the property of becoming a cured product with a glass transition temperature of 80°C or more by curing. In this case, the cured product can have good heat resistance. Therefore, for example, in the case where the cured product is subjected to a treatment accompanied by a temperature rise, the cured product is not easy to deteriorate. Therefore, for example, in the case where the passivation layer 6 is overlapped on the sealing material 5 made of the composition (X) by an evaporation method such as a plasma CVD method, even if the sealing material 5 is heated, the sealing material 5 is not easy to deteriorate. The glass transition temperature of the cured product is more preferably 90°C or more, and further preferably 100°C or more. The glass transition temperature of the cured product can be achieved by the composition of the composition (X) described in detail below.
[0025] The viscosity of the composition (X) at 25°C is preferably 1 mPa·s or more and 30 mPa·s or less. In this case, the composition (X) can be easily molded at room temperature by a method such as a casting method, or the composition (X) can be molded by an inkjet method. The viscosity is more preferably 25 mPa·s or less, further preferably 20 mPa·s or less, and particularly preferably 15 mPa·s or less. The viscosity is also preferably 5 mPa·s or more.
[0026] The viscosity of the composition (X) at 40°C is also preferably 1 mPa·s or more and 30 mPa·s or less. In this case, no matter what the viscosity of the composition (X) at room temperature is, as long as the composition (X) is slightly heated, it can be made low in viscosity. Therefore, if heated, it is easy to mold the composition (X) by a method such as a casting method, and the composition (X) can also be molded by an inkjet method. In addition, since the viscosity can be made low without significantly heating the composition (X), the composition of the composition (X) is not easily changed by the volatilization of the components in the composition (X). The viscosity is more preferably less than 25 mPa·s, further preferably less than 20 mPa·s, and particularly preferably less than 15 mPa·s. The viscosity is also preferably more than 5 mPa·s.
[0027] The viscosity of the composition (X) is measured using a rheometer at a shear rate of 100 s-1. As the rheometer, for example, Model DHR-2 manufactured by Anton Paar Japan can be used.
[0028] Such a low viscosity of the composition (X) at 25° C. or 40° C. can be achieved by the composition of the composition (X) described in detail below.
[0029] The total light transmittance of the cured product of the composition (X) is preferably 90% or more when the thickness dimension is 10 μm. In this case, if the cured product is applied to the sealing material 5 in the organic EL light-emitting device 1, the extraction efficiency of the light emitted to the outside through the sealing material 5 can be particularly improved. The light transmittance of such a cured product can also be achieved by the composition of the composition (X) described in detail below.
[0030] Hereinafter, this embodiment will be described in more detail.
[0031] 1. Structure of organic EL light-emitting device
[0032] First, the structure of the organic EL light-emitting device 1 is described. The organic EL light-emitting device 1 includes an organic EL element 4 and a sealing material 5 covering the organic EL element 4. The sealing material 5 can cover the organic EL element 4 in a state of direct contact with the organic EL element 4, or can cover the organic EL element 4 in a state of interposing some layers between the sealing material 5 and the organic EL element 4. It should be noted that EL is an abbreviation for electroluminescence. In addition, the organic EL element 4 is also called an organic light-emitting diode.
[0033] Reference Figure 1 A first example of the structure of an organic EL light-emitting device 1 is described. The organic EL light-emitting device 1 is a top emission type. The organic EL light-emitting device 1 includes a supporting substrate 2, a transparent substrate 3 opposed to the supporting substrate 2 with a gap therebetween, an organic EL element 4 located on the surface of the supporting substrate 2 opposed to the transparent substrate 3, and a sealing material 5 filled between the supporting substrate 2 and the transparent substrate 3. In addition, in the first example, the organic EL light-emitting device 1 includes a passivation layer 6 covering the surface of the supporting substrate 2 opposed to the transparent substrate 3 and the organic EL element 4. That is, the passivation layer 6 is interposed between the organic EL element 4 and the sealing material 5 covering the organic EL element 4.
[0034] The support substrate 2 is made of, for example, a resin material, but is not limited thereto. The transparent substrate 3 is made of a light-transmitting material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate. The organic EL element 4 includes, for example, a pair of electrodes and an organic light-emitting layer located between the electrodes. The organic light-emitting layer includes, for example, a hole injection layer, a hole transport layer, an organic light-emitting layer, and an electron transport layer, and these layers are stacked in the above order. Figure 1 Only one organic EL element 4 is shown in the figure, but the organic EL light emitting device 1 may also include a plurality of organic EL elements 4, and the plurality of organic EL elements 4 form an array on the supporting substrate 2. The passivation layer 6 is preferably made of silicon nitride or silicon oxide.
[0035] Reference Figure 2 A second example of the structure of the organic EL light emitting device 1 is described. Figure 1The common elements of the first example shown are marked with Figure 1 The same symbols are used and detailed descriptions are appropriately omitted. Figure 2 The organic EL light-emitting device 1 shown is also a top emission type. The organic EL light-emitting device 1 includes a supporting substrate 2, a transparent substrate 3 spaced apart from the supporting substrate 2, an organic EL element 4 located on the surface of the supporting substrate 2 facing the transparent substrate 3, and a sealing material 5 covering the organic EL element 4.
[0036] The organic EL element 4 is similar to the first example, and includes, for example, a pair of electrodes 41 and 43 and an organic light-emitting layer 42 located between the electrodes 41 and 43. The organic light-emitting layer 42 includes, for example, a hole injection layer 421, a hole transport layer 422, an organic light-emitting layer 423, and an electron transport layer 424, and these layers are stacked in the above order.
[0037] The organic EL light-emitting device 1 includes a plurality of organic EL elements 4, and the plurality of organic EL elements 4 form an array 9 (hereinafter referred to as the element array 9) on a supporting substrate 2. The element array 9 also includes a partition wall 7. The partition wall 7 is located on the supporting substrate 2 and separates two adjacent organic EL elements 4. The partition wall 7 is made, for example, by molding a photosensitive resin material using a photolithography method. The element array 9 also includes a connection wiring 8 that electrically connects the electrodes 43 and the electron transport layer 424 of the adjacent organic EL elements 4 to each other. The connection wiring 8 is provided on the partition wall 7.
[0038] The organic EL light emitting device 1 further includes a passivation layer 6 covering the organic EL element 4. The passivation layer 6 is preferably made of silicon nitride or silicon oxide. The passivation layer 6 includes a first passivation layer 61 and a second passivation layer 62. The first passivation layer 61 covers the element array 9 in a state of direct contact with the element array 9, thereby covering the organic EL element 4. The second passivation layer 62 is arranged at a position on the opposite side of the element array 9 relative to the first passivation layer 61, and a gap is separated between the second passivation layer 62 and the first passivation layer 61. The sealing material 5 is filled between the first passivation layer 61 and the second passivation layer 62. That is, the first passivation layer 61 is interposed between the organic EL element 4 and the sealing material 5 covering the organic EL element 4.
[0039] In addition, a second sealing material 52 is filled between the second passivation layer 62 and the transparent substrate 3. The second sealing material 52 is made of, for example, a transparent resin material. There is no particular limitation on the material of the second sealing material 52. The material of the second sealing material 52 can be the same as that of the sealing material 5 or different.
[0040] The sealing material 5 in the organic EL light-emitting device 1 having the above-exemplified structure can be produced from the ultraviolet curable resin composition of this embodiment. That is, the ultraviolet curable resin composition is used to produce the sealing material 5 for the organic EL element 4. In other words, the ultraviolet curable resin composition is preferably a composition for producing a sealing material, a composition for sealing an organic EL element, or a composition for producing an organic EL light-emitting device.
[0041] 2. Ultraviolet curable resin composition
[0042] The ultraviolet curable resin composition (hereinafter, also referred to as composition (X)) of this embodiment will be described.
[0043] As described above, the composition (X) contains an acrylic compound (A) and a photopolymerization initiator (B). When the composition (X) is irradiated with ultraviolet rays, a photo-radical polymerization reaction is initiated by the photopolymerization initiator (B) so that the acrylic compound (A) is cured, thereby producing a cured product. The components of the composition (X) will be described in more detail below.
[0044] As described above, the composition (X) contains an acrylic compound (A). The acrylic compound (A) has one or more (meth)acryloyl groups in one molecule. It should be noted that "(meth)acrylic acid" means at least one of "acrylic acid" and "methacrylic acid".
[0045] The viscosity of the acrylic compound (A) as a whole at 25°C is preferably 50 mPa·s or less. In this case, the acrylic compound (A) can make the composition (X) particularly low in viscosity. More preferably, the viscosity of the acrylic compound (A) as a whole is 30 mPa·s or less, further preferably 25 mPa·s or less, and particularly preferably 20 mPa·s or less. In addition, the viscosity of the acrylic compound (A) as a whole is, for example, 3 mPa·s or more.
[0046] The viscosity of the acrylic compound (A) as a whole at 40°C is preferably 50 mPa·s or less. In this case, the acrylic compound (A) can make the composition (X) particularly low in viscosity when heated. The viscosity of the acrylic compound (A) as a whole is more preferably 30 mPa·s or less, more preferably 25 mPa·s or less, and particularly preferably 20 mPa·s or less. In addition, the viscosity of the acrylic compound (A) as a whole is, for example, 3 mPa·s or more.
[0047] The compounds that may be contained in the acrylic compound (A) are described.
[0048] As described above, the acrylic compound (A) contains an acrylic compound (A1) having a structure represented by formula (1) and having a boiling point of 270° C. or higher. In other words, the acrylic compound (A) contains the acrylic compound (A1), and the acrylic compound (A1) is composed only of at least one compound having a boiling point of 270° C. or higher among the compounds having a structure represented by formula (1).
[0049] Since the boiling point of the acrylic compound (A1) is above 270°C, the acrylic compound (A1) is not easy to volatilize from the composition (X) during the storage of the composition (X) and when the composition (X) is heated. Therefore, it is not easy to damage the storage stability of the composition (X). In addition, even if the acrylic compound (A1) remains unreacted in the cured product of the composition (X) and in the sealing material 5, it is not easy to produce outgassing caused by the acrylic compound (A1) from the cured product and the sealing material 5. Therefore, it is not easy to produce gaps caused by outgassing in the organic EL light-emitting device 1. If there are gaps in the organic EL light-emitting device 1, moisture may reach the organic EL element 4 through the gaps, but if it is not easy to produce gaps, moisture is not easy to reach the organic EL element 4, so the organic EL element 4 is not easy to deteriorate due to moisture. It should be noted that the boiling point is the boiling point under normal pressure obtained by converting the boiling point under reduced pressure, for example, by the method shown in Science of Petroleum, Vol.II.P.1281 (1938). The boiling point of the acrylic compound (A1) is more preferably 280° C. or higher.
[0050] In addition, the acrylic compound (A1) has a structure represented by the formula (1), and in particular, R 3 The number of carbon atoms in the acrylic compound (A1) is 3 or more, so that the acrylic compound (A1) is less likely to increase the affinity between the sealing material 5 and water. Therefore, it is less likely that moisture will penetrate into the organic EL element through the sealing material 5. 3 The number of carbon atoms is, for example, 3 or more and 15 or less. In addition, the acrylic compound (A1) has a structure represented by formula (1), especially having two (meth)acryloyl groups in one molecule, thereby increasing the glass transition temperature of the cured product, thereby increasing the heat resistance of the cured product and the sealing material 5. In addition, n in formula (1) is, for example, an integer of 1 or more and 12 or less.
[0051] The percentage of the acrylic compound (A1) relative to the acrylic compound (A) is 50% by mass or more. Therefore, the storage stability of the composition (X) can be effectively improved, and the outgassing generated from the sealing material 5 can be effectively reduced. In addition, the affinity of the sealing material 5 for water is particularly difficult to improve. In addition, the percentage of the acrylic compound (A1) relative to the acrylic compound (A) is, for example, 100% by mass or less, or 95% by mass or less, and preferably 80% by mass or less.
[0052] The viscosity of the acrylic compound (A1) at 25°C is preferably 25 mPa·s or less. In this case, the acrylic compound (A1) can reduce the viscosity of the composition (X). The viscosity of the acrylic compound (A1) at 25°C is more preferably 25 mPa·s or less, further preferably 20 mPa·s or less, and particularly preferably 15 mPa·s or less. In addition, the viscosity of the acrylic compound (A1) at 25°C is, for example, 1 mPa·s or more, preferably 3 mPa·s or more, and further preferably 5 mPa·s or more.
[0053] The acrylic compound (A1) contains at least one compound selected from, for example, di(meth)acrylates of alkylene glycols, di(meth)acrylates of polyalkylene glycols, and di(meth)acrylates of alkylene glycols modified with alkylene oxides.
[0054] The di(meth)acrylate of alkylene glycol is a compound wherein n is 1 in formula (1). In this case, R in formula (1) 3 The number of carbon atoms in R is preferably 4 to 12. 3It may be straight chain or branched. In particular, the di(meth)acrylate of alkylene glycol preferably contains at least one compound selected from 1,4-butanediol diacrylate, 1,3-butanediol diacrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, 1,4-butanediol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, and 1,12-dodecanediol dimethacrylate. The di(meth)acrylate of alkylene glycol preferably contains a product selected from the group consisting of SR213 manufactured by Sartomer, V195 manufactured by Osaka Organic Chemical Industry Co., Ltd., SR212 manufactured by Sartomer, SR247 manufactured by Sartomer, LIGHT ACRYLATE manufactured by Kyoei Chemical Industry Co., Ltd. NP-A, product number SR238NS manufactured by Sartomer, product number V230 manufactured by Osaka Organic Chemical Industry Co., Ltd., product number HDDA manufactured by Daicel, product number 1,6HX-A manufactured by Kyoei Chemical Industry Co., Ltd., product number V260 manufactured by Osaka Organic Chemical Industry Co., Ltd., product number 1,9-ND-A manufactured by Kyoei Chemical Industry Co., Ltd., product number A-NOD-A manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product number CD595 manufactured by Sartomer, product number SR214NS manufactured by Sartomer, product number BD manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product number SR297 manufactured by Sartomer, product number SR248 manufactured by Sartomer, product name LIGHT ESTER NP manufactured by Kyoei Chemical Industry Co., Ltd., product number SR239NS manufactured by Sartomer, product name LIGHT ESTER manufactured by Kyoei Chemical Industry Co., Ltd. 1,6HX, product number HD-N manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name LIGHT ESTER 1,9ND manufactured by Kyoei Chemical Industry Co., Ltd., product number NOD-N manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name LIGHT ESTER 1,10DC manufactured by Kyoei Chemical Industry Co., Ltd., product number DOD-N manufactured by Shin-Nakamura Chemical Industry Co., Ltd., and at least one compound selected from the group consisting of product number SR262 manufactured by Sartomer.
[0055] The di(meth)acrylate of polyalkylene glycol is a compound wherein n in formula (1) is 2 or more. n is, for example, 2 to 10, preferably 2 to 7, more preferably 2 to 6, and even more preferably 2 to 3. 3The number of carbon atoms is, for example, 2 to 5. The greater the number of carbon atoms, the higher the hydrophobicity of the cured product and the sealing material 5, and the less likely it is that water will penetrate the sealing material 5. The di(meth)acrylate of the polyalkylene glycol particularly preferably contains at least one compound selected from diethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, hexaethylene glycol dimethacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tripropylene glycol dimethacrylate, and tritetramethylene glycol diacrylate. The polyalkylene glycol di(meth)acrylate is particularly preferably selected from the group consisting of product number SR230 manufactured by Sartomer, product number SR508NS manufactured by Sartomer, product number DPGDA manufactured by Daicel, product number SR306NS manufactured by Sartomer, product number TPGDA manufactured by Daicel, product number V310HP manufactured by Osaka Organic Chemical Industry Co., Ltd., product number APG200 manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name LIGHT ACRYLATE PTMGA-250 manufactured by Kyoei Chemical Industry Co., Ltd., product number SR231NS manufactured by Sartomer, product name LIGHT ESTER 2EG manufactured by Kyoei Chemical Industry Co., Ltd., product number SR205NS manufactured by Sartomer, product name LIGHT ESTER 3EG manufactured by Kyoei Chemical Industry Co., Ltd., product number SR210NS manufactured by Sartomer, product name LIGHT ESTER At least one compound selected from the group consisting of 4EG, ACRYESTER HX (product name) manufactured by Mitsubishi Chemical Corporation, and 3PG (product name) manufactured by Shin-Nakamura Chemical Industry Co., Ltd.
[0056] The di(meth)acrylate of alkylene oxide-modified alkylene glycol includes, for example, propylene oxide-modified neopentyl glycol. The di(meth)acrylate of alkylene oxide-modified alkylene glycol includes, for example, EBECRYL145 manufactured by Daicel Corporation.
[0057] It is preferred that the percentage of components having a boiling point of 270° C. or higher in the acrylic compound (A) is 80% by mass or higher. When the acrylic compound (A) further contains a compound other than the acrylic compound (A1), it is preferred that the percentage of components having a boiling point of 270° C. or higher in all components including the acrylic compound (A) and the compound other than the acrylic compound (A1) in the acrylic compound (A) is 80% by mass or higher. In this case, the storage stability of the composition (X) is particularly unlikely to be impaired, and outgassing from the cured product and the sealing material 5 is particularly unlikely to occur. It is further preferred that the percentage of components having a boiling point of 280° C. or higher in the acrylic compound (A) is 80% by mass or higher.
[0058] The compounds other than the acrylic compound (A1) which may be contained in the acrylic compound (A) are described.
[0059] The acrylic compound (A) may further contain a multifunctional acrylic compound (A2) other than the acrylic compound (A1). The multifunctional acrylic compound (A2) can increase the glass transition temperature of the cured product, thereby increasing the heat resistance of the cured product and the sealing material 5. The multifunctional acrylic compound (A2) contains, for example, polyethylene glycol di(meth)acrylate.
[0060] The multifunctional acrylic compound (A2) preferably contains a compound (A21) having three or more (meth)acryloyl groups in one molecule. That is, the acrylic compound (A) preferably contains the compound (A21). In this case, the compound (A21) may contain, for example, at least one selected from trimethylolpropane triacrylate and trimethylolpropane trimethacrylate. When the acrylic compound (A) contains the compound (A21), the compound (A21) can particularly increase the glass transition temperature of the cured product, and therefore, can particularly increase the heat resistance of the cured product and the sealing material 5.
[0061] When the acrylic compound (A) includes compound (A21), the percentage of compound (A21) relative to the acrylic compound (A) is preferably greater than 0% by mass and less than 25% by mass. The percentage of component (A3) is more preferably more than 10% by mass. In this case, the glass transition temperature of the cured product can be particularly improved. In addition, if compound (A21) is less than 25% by mass, the viscosity increase of the composition (X) caused by compound (A21) is not likely to occur. If the percentage of compound (A21) is less than 20% by mass, the viscosity increase of the composition (X) is particularly not likely to occur.
[0062] The acrylic compound (A) may further contain a monofunctional acrylic compound (A3) having only one (meth) acryloyl group in one molecule. The monofunctional acrylic compound (A3) can suppress the shrinkage of the composition (X) during curing. In addition, the monofunctional acrylic compound (A3) can help reduce the viscosity of the composition (X). In the case where the acrylic compound (A) contains a monofunctional acrylic compound (A3), the percentage of the monofunctional acrylic compound (A3) relative to the total amount of the acrylic compound (A) is preferably greater than 0% by mass and less than 70% by mass. If the percentage of the monofunctional acrylic compound (A3) is greater than 0% by mass, the shrinkage of the composition (X) during curing can be suppressed by the monofunctional acrylic compound (A3). The percentage of the monofunctional acrylic compound (A3) is further preferably 5% by mass or more. If the percentage of the monofunctional acrylic compound (A3) is less than 70% by mass, it is not easy to produce outgassing caused by the monofunctional acrylic compound (A3) from the composition (X) and the cured product. In addition, when the amount of the monofunctional acrylic compound (A3) is 70% by mass or less, the amount of the polyfunctional component in the acrylic compound (A) can be ensured, so the heat resistance of the cured product and the sealing material 5 can be particularly improved by the polyfunctional component. The percentage of the monofunctional acrylic compound (A3) is more preferably 50% by mass or less, the monofunctional acrylic compound (A3) is further preferably 40% by mass or less, and particularly preferably 30% by mass or less.
[0063] The monofunctional acrylic compound (A3) contains, for example, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isooctyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 2-ethoxy (meth)acrylate, ethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxydihexylethyl (meth)acrylate, ethyldiethylene glycol (meth)acrylate, cyclic trimethylolpropane formal mono(meth)acrylate, imide (meth)acrylate, isopentyl (meth)acrylate, ethoxylated succinic acid (meth)acrylate, trifluoroethyl (meth)acrylate, ω-carboxypolycaprolactone mono(meth)acrylate, cyclohexyl (meth)acrylate, 2-(2-ethoxyethoxy) (meth)acrylate Ethyl (meth)acrylate, stearyl (meth)acrylate, diethylene glycol monobutyl ether (meth)acrylate, lauryl (meth)acrylate, isodecyl (meth)acrylate, isooctyl (meth)acrylate, octyl / decyl (meth)acrylate, tridecyl (meth)acrylate, caprolactone (meth)acrylate, ethoxylated (4) nonylphenol (meth)acrylate, methoxy polyethylene glycol (350) mono(meth)acrylate, methoxy polyethylene glycol (550) mono(meth)acrylate, phenoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate , benzyl (meth)acrylate, methylphenoxyethyl (meth)acrylate, caprolactone-modified tetrahydrofurfuryl (meth)acrylate, tribromophenyl (meth)acrylate, ethoxylated tribromophenyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, ethylene oxide adduct of 2-phenoxyethyl (meth)acrylate, propylene oxide adduct of 2-phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 3-methacryloyloxymethyl oxirane, and at least one compound selected from 3-(meth)acryloyloxymethyl oxirane.
[0064] The monofunctional acrylic compound (A3) preferably contains a compound having an alicyclic structure. The compound having an alicyclic structure, for example, contains at least one compound selected from cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, caprolactone-modified tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, and 4-tert-butylcyclohexyl (meth)acrylate.
[0065] The monofunctional acrylic compound (A3) also preferably contains a compound (A31) represented by the following formula (10). In this case, it is easy to reduce the viscosity of the composition (X), and it is easy to impart adhesion to the sealing material 5 made of the composition (X) and the parts made of inorganic materials such as the passivation layer 6. In addition, although the compound (A31) has a low viscosity, it has a property of not being easily volatile. Therefore, even if the composition (X) is preserved, the composition (X) is not easily subject to changes in composition due to the volatilization of the monofunctional acrylic compound (A3).
[0066] [Chemical formula 1]
[0067]
[0068] In formula (10), R 0 is H or methyl. X is a single bond or a divalent hydrocarbon group. 1 ~R 11 H, alkyl or -R 12 -OH, R 12 is an alkylene group and R 1 ~R 11 At least one of them is alkyl or -R 12 -OH.R 1 ~R 11 Not chemically bonded to each other.
[0069] When X is a divalent hydrocarbon group, the number of carbon atoms of X is preferably 1 or more and 5 or less, more preferably 1 or more and 3 or less. The divalent hydrocarbon group is, for example, a methylene group, an ethylene group or a propylene group. It is particularly preferred that X is a single bond or a methylene group. In this case, compound (A31) has the advantages of a small molecular weight and low viscosity.
[0070] In R 1 ~R 11In the case where at least one of the alkyl groups is an alkyl group, the number of carbon atoms of the alkyl group is preferably greater than 1 and less than 8. The alkyl group is, for example, methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl or octyl. The alkyl group may be linear or branched. That is, for example, when the alkyl group is a butyl group, the butyl group may be a tert-butyl group, an n-butyl group or a sec-butyl group. When the alkyl group is a hexyl group, the hexyl group may be a tert-hexyl group, an n-hexyl group or a sec-hexyl group. When the alkyl group is an octyl group, the octyl group may be, for example, a tert-octyl group. The alkyl group is particularly preferably a methyl group or a tert-butyl group. In this case, compound (A31) has the advantages of a small molecular weight and low viscosity.
[0071] In formula (10), it is preferred that an alkyl group or -R 12 -OH. That is, preferably in R 1 ~R 11 In, R 6 and R 7 At least one of them is alkyl or -R 12 -OH, and the rest are each H. It is particularly preferred that R 1 ~R 11 In, only R 6 is alkyl or -R 12 -OH, and the rest are H. In this case, the compound represented by formula (10) can have good reactivity and can easily provide the sealing material 5 with adhesion to the inorganic material component. This is considered to be because the cyclohexane ring in the compound represented by formula (10) has a boat-shaped stereo conformation, and the bulky alkyl group or -R at the 4-position 12 -OH is likely to be located in a nearly flat position. It is believed that by having such a structure in the compound represented by formula (10), the reactivity of the (meth)acryloyl group in the compound represented by formula (10) can be improved. In addition, if the compound represented by formula (10) has such a structure, the compound represented by formula (10) can increase the free volume in the sealing material 5. Therefore, it is believed that the interfacial free energy between the sealing material 5 and the parts made of inorganic materials is likely to be reduced, and thus the adhesion between the sealing material 5 and the parts made of inorganic materials is likely to be increased. Alkyl or -R 12 The larger the -OH volume, the larger the alkyl or -R 12 -OH is more likely to be located in a nearly flat position. From this point of view, the alkyl group or -R 12 -OH is more preferred as it has more carbon atoms. In addition, alkyl or -R 12 -OH has a branched chain. For example, an alkyl group or -R 12 -OH is tert-butyl.
[0072] In formula (10), it is also preferred that an alkyl group or -R 12-OH. That is, preferably in R 1 ~R 11 In, R 4 and R 5 At least one of them is alkyl or -R 12 -OH, R 8 and R 9 At least one of them is alkyl or -R 12 -OH, and the rest are each H. More preferably, R 1 ~R 11 In, only R 4 and R 5 One of them is alkyl or -R 12 -OH, R 8 and R 9 At least one of them is alkyl or -R 12 -OH, and the rest are each H. More preferably, R 1 ~R 11 In, R 4 and R 5 At least one of them is alkyl or -R 12 -OH, R only 8 and R 9 One of them is alkyl or -R 12 -OH, and the rest are H. In this case, the compound represented by formula (10) can also have good reactivity and can easily provide the sealing material 5 with adhesion to the inorganic material component. This is considered to be because the cyclohexane ring in the compound represented by formula (10) has a boat-shaped stereo conformation, and the 3- and 5-positions are each bulky alkyl or -R 12 -OH is easily located in a nearly flat position. Therefore, it is believed that the alkyl group or -R 12 In the case of -OH, the reactivity of the (meth)acryloyl group in the compound represented by formula (10) is improved, and the adhesion between the sealing material 5 and the inorganic material member is likely to be improved. 12 The larger the -OH volume, the larger the alkyl or -R 12 -OH is more likely to be located in a nearly flat position. From this point of view, the alkyl group or -R 12 -OH is more preferred as it has more carbon atoms. In addition, alkyl or -R 12 -OH has a branched chain. For example, an alkyl group or -R 12 -OH is tert-butyl.
[0073] In R 1 ~R 11 At least one of them is -R 12 In the case of -OH, R 12 The number of carbon atoms in is preferably 1 or more and 5 or less, more preferably 1 or more and 3 or less.12 For example, it is methylene, ethylene or propylene. 12 In this case, the compound (A31) has the advantages of small molecular weight and low viscosity.
[0074] In formula (10), R is particularly preferably 1 ~R 11 Each is H or alkyl, and R 1 ~R 11 At least one of them is an alkyl group. In this case, the compound represented by formula (10) can have a particularly low viscosity, and therefore, the composition (X) can have a particularly low viscosity. Therefore, it is particularly easy to mold the composition (X) by an inkjet method.
[0075] The compound (A31) preferably contains at least one compound selected from the group consisting of a compound represented by the following formula (11), a compound represented by the following formula (12), and a compound represented by the following formula (13).
[0076] [Chemical formula 2]
[0077]
[0078] It is particularly preferred that the monofunctional acrylic compound (A3) contains at least one of the compound represented by formula (11) and the compound represented by formula (12). In this case, it is particularly easy to reduce the viscosity of the composition (X), and it is particularly easy to increase the glass transition temperature of the sealing material 5, and it is particularly easy to increase the adhesion between the sealing material 5 and the parts made of inorganic materials. In addition, since the compound represented by formula (11) and the compound represented by formula (12) are not easy to volatilize, it is easy to improve the storage stability of the composition (X).
[0079] The monofunctional acrylic compound (A3) also preferably contains a compound having a cyclic ether structure. The number of ring members of the cyclic ether structure in the compound having a cyclic ether structure is preferably 3 or more, more preferably 3 or more and 4 or less. The number of carbon atoms contained in the cyclic ether structure is preferably 2 or more and 9 or less, more preferably 2 or more and 6 or less. The compound having a cyclic ether structure contains, for example, at least one compound selected from 3-methacryloyloxymethyloxirane and 3-acryloyloxymethyloxirane.
[0080] The monofunctional acrylic compound (A3) preferably contains at least one compound having a viscosity of 20 mPa·s or less at 25° C. In this case, the viscosity of the composition (X) can be reduced.
[0081] The monofunctional acrylic compound (A3) preferably contains at least one compound having a glass transition temperature of 80°C or higher. In this case, the cured product of the composition (X) can have a high glass transition temperature. The monofunctional acrylic compound (A3) more preferably contains at least one compound having a glass transition temperature of 90°C or higher, and further preferably contains at least one compound having a glass transition temperature of 100°C or higher.
[0082] The monofunctional acrylic compound (A3) preferably contains at least one compound having a boiling point of 200° C. or higher. In this case, the monofunctional acrylic compound (A3) is less likely to reduce the storage stability of the composition (X). The monofunctional acrylic compound (A3) further preferably contains at least one compound having a boiling point of 250° C. or higher.
[0083] The monofunctional acrylic compound (A3) particularly preferably contains at least one compound having a viscosity of 20 mPa·s or less at 25°C and a glass transition temperature of 80°C or more. The monofunctional acrylic compound (A3) also preferably contains at least one compound having a viscosity of 20 mPa·s or less at 25°C and a boiling point of 200°C or more. The monofunctional acrylic compound (A3) also preferably contains at least one compound having a glass transition temperature of 80°C or more and a boiling point of 200°C or more. The monofunctional acrylic compound (A3) particularly preferably contains at least one compound having a viscosity of 20 mPa·s or less at 25°C, a glass transition temperature of 80°C or more and a boiling point of 200°C or more.
[0084] It is particularly preferred that the monofunctional acrylic compound (A3) contains at least one compound selected from the group consisting of isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, and 4-tert-butylcyclohexyl (meth)acrylate. Isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, and 4-tert-butylcyclohexyl (meth)acrylate have high glass transition temperatures, low viscosities, and high boiling points, and thus can particularly improve the properties of the composition (X), the curing agent, and the sealing material 5.
[0085] The acrylic compound (A) preferably further contains at least one compound selected from a compound having silicon in its molecular skeleton (A41), a compound having phosphorus in its molecular skeleton (A42), and a compound having nitrogen in its molecular skeleton (A43). In this case, the adhesion between the cured product and the sealing material 5 and the inorganic material component is improved. Therefore, it is difficult to generate a gap between the sealing material 5 and the passivation layer 6, and it is difficult for moisture to intrude into the organic EL element 4 through the gap.
[0086] It should be noted that the compounds (A41), (A42) and (A43) are defined by the types of atoms present in the molecular skeleton. Therefore, the compounds contained in the multifunctional acrylic compound (A2) and the monofunctional acrylic compound (A3) may overlap with the compounds contained in the compounds (A41), (A42) and (A43).
[0087] Compound (A41) contains, for example, at least one compound selected from 3-(trimethoxysilyl)propyl acrylate (e.g., product number KBM5103 manufactured by Shin-Etsu Chemical Co., Ltd.) and a (meth)acrylic group-containing alkoxysilane oligomer (e.g., product number KR-513 manufactured by Shin-Etsu Chemical Co., Ltd.). However, since the boiling point of 3-(trimethoxysilyl)propyl acrylate is 260° C., when the acrylic compound (A) contains 3-(trimethoxysilyl)propyl acrylate, the percentage of 3-(trimethoxysilyl)propyl acrylate relative to the acrylic compound (A) needs to be 10% by mass or less.
[0088] Compound (A42) includes, for example, acidic phosphonooxy (meth)acrylates such as acidic phosphonooxy polyoxypropylene glycol monomethacrylate.
[0089] The compound (A43) contains, for example, at least one compound selected from the group consisting of acryloylmorpholine, diethylacrylamide, dimethylaminopropylacrylamide, and pentamethylpiperidinyl methacrylate.
[0090] When the acrylic compound (A) contains at least one compound selected from the group consisting of compound (A41), compound (A42) and compound (A43), the total amount of compound (A41), compound (A42) and compound (A43) relative to the acrylic compound (A) is preferably from 0.5 mass % to 20 mass %, more preferably from 1 mass % to 15 mass %.
[0091] The composition (X) may further contain a radical polymerizable compound (E) other than the acrylic compound (A). The radical polymerizable compound (E) may contain any one or both of a polyfunctional radical polymerizable compound (E1) having two or more radical polymerizable functional groups in one molecule and a monofunctional radical polymerizable compound (E2) having only one radical polymerizable functional group in one molecule. The amount of the radical polymerizable compound (E) is, for example, 10% by mass or less relative to the total amount of the acrylic compound (A) and the radical polymerizable compound (E). The polyfunctional radical polymerizable compound (E1) may, for example, contain at least one compound selected from aromatic carbamate oligomers, aliphatic carbamate oligomers, epoxy acrylate oligomers, polyester acrylate oligomers and other special oligomers having two or more ethylenic double bonds in one molecule. The monofunctional free radical polymerizable compound (E2) contains at least one compound selected from, for example, N-vinylformamide, vinyl caprolactam, vinyl pyrrolidone, phenyl glycidyl ether, p-tert-butylphenyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, allyl glycidyl ether, 1,2-butylene oxide, 1,3-butadiene monoxide, 1,2-epoxydodecane, epichlorohydrin, 1,2-epoxydecane, styrene oxide, hexyl oxide, 3-vinylcyclohexene oxide, 4-vinylcyclohexene oxide, N-vinylpyrrolidone and N-vinylcaprolactam.
[0092] Photopolymerization initiator (B) is not particularly limited as long as it is a compound that generates free radical species when irradiated with ultraviolet rays. Photopolymerization initiator (B) contains, for example, at least one compound selected from aromatic ketones, acylphosphine oxide compounds, aromatic onium salt compounds, organic peroxides, sulfur compounds (thioxanthone compounds, compounds containing thiophenyl, etc.), hexaaryl biimidazole compounds, ketoxime ester compounds, borate compounds, azinium compounds, metallocene compounds, active ester compounds, compounds having carbon-halogen bonds, and alkylamine compounds. Relative to 100 parts by mass of composition (X), the amount of photopolymerization initiator (B) is, for example, 1 part by weight or more and 10 parts by mass or less.
[0093] The photopolymerization initiator (B) may contain a sensitizer as a part of the photopolymerization initiator (B). The sensitizer can promote the free radical generation reaction of the photopolymerization initiator (B), improve the reactivity of free radical polymerization, and increase the crosslinking density. The sensitizer may contain, for example, at least one compound selected from 9,10-dibutoxyanthracene, 9-hydroxymethylanthracene, thioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, anthraquinone, 1,2-dihydroxyanthraquinone, 2-ethylanthraquinone, 1,4-diethoxynaphthalene, p-dimethylaminoacetophenone, p-diethylaminoacetophenone, p-dimethylaminobenzophenone, p-diethylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, p-dimethylaminobenzaldehyde, and p-diethylaminobenzaldehyde.
[0094] The content of the sensitizer in the composition (X) is, for example, 0.1 parts by mass or more and 5 parts by mass or less, and preferably 0.1 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the solid content of the composition (X). When the content of the sensitizer is within such a range, the composition (X) can be cured in air, and there is no need to perform curing of the composition (X) in an inert atmosphere such as a nitrogen atmosphere.
[0095] The composition (X) may contain a polymerization accelerator in addition to the photopolymerization initiator (B). The polymerization accelerator includes, for example, an amine compound such as ethyl p-dimethylaminobenzoate, 2-ethylhexyl p-dimethylaminobenzoate, methyl p-dimethylaminobenzoate, 2-dimethylaminoethyl benzoate, and butoxyethyl p-dimethylaminobenzoate.
[0096] The composition (X) may further contain a hygroscopic agent (D). If the composition (X) contains a hygroscopic agent (D), the cured product of the composition (X) and the sealing material 5 can have hygroscopicity. Therefore, the sealing material 5 can make it more difficult for moisture to invade the organic EL element 4 in the organic EL light-emitting device 1. The average particle size of the hygroscopic agent (D) is preferably less than 200nm. In this case, the cured product can have high transparency.
[0097] The moisture absorbent (D) is preferably hygroscopic inorganic particles, and preferably contains at least one component selected from zeolite particles, silica gel particles, calcium chloride particles, and titanium oxide nanotube particles. The moisture absorbent (D) particularly preferably contains zeolite particles.
[0098] The zeolite particles with an average particle size of less than 200 nm can be manufactured, for example, by crushing common industrial zeolites. When manufacturing the zeolite particles, the zeolite can be crystallized by hydrothermal synthesis after being crushed, in which case the zeolite particles can have particularly high hygroscopicity. Examples of the manufacturing methods of such zeolite particles are disclosed in Japanese Patent Publication No. 2016-69266, Japanese Patent Publication No. 2013-049602, etc.
[0099] When the composition (X) contains a hygroscopic agent (D), the ratio of the hygroscopic agent (D) relative to the total amount of the composition (X) is preferably 1% by mass or more and 20% by mass or less. If the ratio of the hygroscopic agent (D) is 1% by mass or more, the cured product can have a particularly high hygroscopicity. In addition, if the ratio of the hygroscopic agent (D) is 20% by mass or less, the viscosity of the composition (X) can be particularly reduced, and the composition (X) can also have a sufficiently low viscosity to the extent that it can be applied by an inkjet method. The ratio of the hygroscopic agent (D) is further preferably 3% by mass or more, particularly preferably 5% by mass or more. In addition, the ratio of the hygroscopic agent (D) is more preferably 15% by mass or less, particularly preferably 13% by mass or less.
[0100] When the composition (X) contains a hygroscopic agent (D), the composition (X) preferably further contains a dispersant (E). In this case, the dispersant (E) can improve the dispersibility of the hygroscopic agent (D) in the composition (X). Therefore, in the composition (X), an increase in viscosity and a decrease in storage stability due to the hygroscopic agent (D) are unlikely to occur.
[0101] It should be noted that the dispersant (E) is a surfactant that can be adsorbed on particles. The dispersant (E) has an adsorption group (also generally referred to as an anchor) that can be adsorbed on particles and a molecular skeleton (also generally referred to as a tail) that is attached to the particle by adsorption of the adsorption group on the particle. The dispersant (E) contains, for example, at least one component selected from the following dispersants: an acrylic dispersant whose tail is an acrylic molecular chain, a carbamate dispersant whose tail is a carbamate molecular chain, and a polyester dispersant whose tail is a polyester molecular chain. The adsorption group, for example, includes at least one of a basic polar functional group and an acidic polar functional group. The basic polar functional group, for example, includes at least one group selected from an amino group, an imino group, an amide group, an imide group, and a nitrogen-containing heterocyclic group. The acidic polar functional group, for example, includes at least one group selected from a carboxyl group and a phosphate group. The dispersant (E) may contain at least one compound selected from, for example, Solsperse series manufactured by Nippon Lubrizo Co., Ltd., DISPERBYK series manufactured by BYK-Chemie Japan Co., Ltd., and Ajisper series manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0102] When the composition (X) contains a hygroscopic agent (D), the amount of the dispersant (E) relative to the hygroscopic agent (D) is preferably 5 parts by mass or more and 60 parts by mass or less. When the amount of the dispersant (E) is 5 parts by mass or more, the function of the dispersant (E) can be effectively exhibited, and when it is 60 parts by mass or less, it is possible to suppress the free molecules of the dispersant (E) in the sealing material 5 from hindering the adhesion between the sealing material 5 and the inorganic material component. In addition, the amount of the dispersant (D) is more preferably 15 parts by mass or more, more preferably 50 parts by mass or less, further preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less.
[0103] The composition (X) preferably does not contain a solvent. In this case, when a cured product is prepared from the composition (X), it is not necessary to dry the composition (X) to volatilize the solvent. In addition, the storage stability of the composition (X) is further improved.
[0104] The composition (X) can be prepared by mixing the above components. The composition (X) is preferably in a liquid state at 25°C.
[0105] 3. Method for manufacturing sealing material and method for manufacturing organic EL light-emitting device
[0106] A method for producing the sealing material 5 and a method for producing the organic EL light-emitting device 1 using the composition (X) will be described.
[0107] In this embodiment, it is preferred that after the composition (X) is molded by an inkjet method, the composition (X) is irradiated with ultraviolet rays to be cured, thereby producing the sealing material 5. In this embodiment, the composition (X) can be molded by applying it by an inkjet method.
[0108] When the composition (X) is applied by an inkjet method, if the composition (X) has a sufficiently low viscosity at room temperature, for example, a viscosity at 25°C of 30 mPa·s or less, particularly 15 mPa·s or less, the composition (X) can be applied by an inkjet method to form a film without heating the composition (X).
[0109] When the composition (X) has a property of decreasing viscosity by heating, the composition (X) can be molded by applying the composition (X) by an inkjet method after heating the composition (X). When the viscosity of the composition (X) at 40°C is 30 mPa·s or less, particularly 15 mPa·s or less, the viscosity of the composition (X) can be decreased by simply heating the composition (X) slightly, and the composition (X) with decreased viscosity can be discharged by an inkjet method. The heating temperature of the composition (X) is, for example, 20°C or more and 50°C or less.
[0110] More specifically, for example, a support substrate 2 is first prepared. For example, a photosensitive resin material is used and a partition wall 7 is formed on one surface of the support substrate 2 by photolithography. Next, a plurality of organic EL elements 4 are provided on one surface of the support substrate 2. The organic EL element 4 can be produced by an appropriate method such as a vapor deposition method or a coating method. It is particularly preferred to produce the organic EL element 4 by a coating method such as an inkjet method. Thus, an element array 9 is produced on the support substrate 2.
[0111] Next, the first passivation layer 61 is provided on the element array 9. The first passivation layer 61 can be formed by a vapor deposition method such as a plasma CVD method.
[0112] Next, the composition (X) is molded on the first passivation layer 61 by, for example, an inkjet method to form a coating film. If the inkjet method is applied to both the formation of the organic EL element 4 and the coating of the composition (X), the manufacturing efficiency of the organic EL light-emitting device 1 can be particularly improved. Next, the coating film is cured by irradiating ultraviolet rays to form a sealing material 5. The thickness of the sealing material 5 is, for example, 5 μm or more and 50 μm or less.
[0113] Next, the second passivation layer 62 is provided on the sealing material 5. The second passivation layer 62 can be formed by a vapor deposition method such as a plasma CVD method.
[0114] Next, after an ultraviolet curable resin material is provided on one surface of the support substrate 2 so as to cover the second passivation layer 62, the transparent substrate 3 is stacked on the resin material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate.
[0115] Next, ultraviolet rays are irradiated from the outside to the transparent substrate 3. The ultraviolet rays pass through the transparent substrate 3 and reach the ultraviolet curable resin material. As a result, the ultraviolet curable resin material is cured, and the second sealing material 52 is produced.
[0116] Example
[0117] 1. Preparation of the composition
[0118] The compositions of Examples and Comparative Examples were prepared by mixing the components shown in the following table.
[0119] It should be noted that the details of the components shown in the table are as follows. In addition, the viscosity of each component below was measured using a rheometer (manufactured by Anton Paar Japan, model DHR-2) at a temperature of 25°C and a shear rate of 1000 s -1 The value measured under the conditions of .
[0120] (1) Acrylic compounds
[0121] - KBM5103: 3-(trimethoxysilyl)propyl acrylate which is a monofunctional acrylic compound having a silicon atom, product number KBM5103 manufactured by Shin-Etsu Chemical Co., Ltd., viscosity 4 mPa·s, refractive index 1.427, boiling point 260.
[0122] - KR513: an acrylic group-containing alkoxysilane oligomer which is a trifunctional or higher-functional acrylic compound having a silicon atom, having a viscosity of 50 mPa·s, a refractive index of 1.427, and a boiling point of 300° C. or higher.
[0123] - LIGHT ESTER P-2M: 2-methacryloyloxyethyl acid phosphate, manufactured by Kyoeisha Chemical Co., Ltd., product name LIGHT ESTER P-2M, viscosity 800 mPa·s, refractive index 1.4673, boiling point 300 or higher.
[0124] -ACMO: acryloylmorpholine, manufactured by KJ Chemical, viscosity 12 mPa·s, glass transition temperature 145°C.
[0125] -3PG: tripropylene glycol dimethacrylate as a difunctional acrylic compound, manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product number 3PG, viscosity 13 mPa·s, glass transition temperature -8°C, refractive index 1.450, boiling point 400°C.
[0126] - APG200: tripropylene glycol diacrylate as a difunctional acrylic compound, manufactured by Shin-Nakamura Chemical Industry Co., Ltd., with a viscosity of 12 mPa·s, a glass transition temperature of 55 to 62°C, a refractive index of 1.449, and a boiling point of 295°C.
[0127] -SR297: 1,3-Butanediol dimethacrylate as a difunctional acrylic compound, manufactured by Sartomer, product number SR297, viscosity 7 mPa·s, glass transition temperature 85°C, refractive index 1.449, boiling point 290°C.
[0128] -EBECRYL145: Propylene oxide-modified neopentyl glycol diacrylate as a difunctional acrylic compound, manufactured by DAICEL ALLNEX, product number EBECRYL145, viscosity 20 mPa·s, glass transition temperature 60°C, refractive index 1.459, boiling point 408°C.
[0129] -BD: 1,4-Butanediol dimethacrylate as a bifunctional acrylic compound, manufactured by Shin-Nakamura Chemical Industry Co., Ltd., with a viscosity of 7 mPa·s, a glass transition temperature of 55°C, a refractive index of 1.456, and a boiling point of 280°C.
[0130] -SR351S: trimethylolpropane triacrylate as a trifunctional acrylic compound, viscosity 106 mPa·s, glass transition temperature 62° C., refractive index 1.472, boiling point 300° C. or higher, manufactured by Sartomer, product number SR351S.
[0131] -SR350NS: trimethylolpropane trimethacrylate as a trifunctional acrylic compound, viscosity 44 mPa·s, glass transition temperature 27° C., refractive index 1.470, boiling point 300° C. or higher, manufactured by Sartomer, product number SR350NS.
[0132] -SR295NS: Pentaerythritol tetraacrylate as a tetrafunctional acrylic compound, viscosity 342 mPa·s, glass transition temperature 103° C., refractive index 1.485, boiling point 300° C. or higher, manufactured by Sartomer, product number SR295NS.
[0133] -SR210NS: polyethylene glycol 200 dimethacrylate, viscosity 15 mPa·s, glass transition temperature -9°C, refractive index 1.460, boiling point 350°C, manufactured by Sartomer, product number SR210NS.
[0134] -VEEA: 2-(2-vinyloxyethoxy)ethyl acrylate as a bifunctional free radical polymerizable compound, viscosity 4 mPa·s, glass transition temperature 40°C, boiling point 260°C, manufactured by Nippon Shokubai.
[0135] -IBXA: isobornyl acrylate as a monofunctional acrylic compound, glass transition temperature 97°C, viscosity 8 mPa·s, boiling point 260°C, manufactured by Osaka Organic Chemical Co., Ltd.
[0136] FA-513AS: dicyclopentanyl acrylate as a monofunctional acrylic compound, glass transition temperature 120° C., viscosity 13 mPa·s, boiling point 275° C., manufactured by Hitachi Chemical Co., Ltd., product number FA-513AS.
[0137] (2) Photopolymerization initiator
[0138] - Irgacure 184: 1-hydroxy-cyclohexyl-phenyl-ketone, manufactured by BASF, product name Irgacure 184.
[0139] -Irgacure TPO: 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, manufactured by BASF, product name Irgacure TPO.
[0140] 2. Evaluation test
[0141] The following evaluation tests were carried out on the Examples and Comparative Examples, and the results are shown in the table.
[0142] (1) Transmittance
[0143] The composition was applied to form a coating film, and an LED-UV irradiator (peak wavelength 365 nm) manufactured by Panasonic Electric Works Co., Ltd. was used at a power of about 50 mW / cm 2 The coating film was irradiated with ultraviolet rays for 30 seconds under the conditions of , and photocured to prepare a film having a thickness of 10 μm. The total light transmittance of the film was measured in accordance with JIS K7361-1.
[0144] (2) Adhesion after moisture absorption
[0145] A 1 μm thick silicon nitride film was made on each surface of two quartz glass sheets (size 76 mm × 52 mm × 1 mm) by plasma CVD method to obtain two substrates. The composition was applied to the surface of the silicon nitride film of one substrate to form a coating film with a thickness of 200 μm, and the silicon nitride film of the other substrate was overlapped on the coating film. Next, an LED-UV irradiator (peak wavelength 365 nm) manufactured by Panasonic Electric Co., Ltd. was used at about 50 mW / cm 2 The coating film was irradiated with ultraviolet rays for 30 seconds under the conditions of , and cured. Thus, a test piece was obtained.
[0146] After the test piece was exposed to an atmosphere of 85°C and 85RH, the interface between the coating and the silicon nitride film was confirmed with a microscope. The results were evaluated as follows. It should be noted that in this test, the higher the adhesion between the coating and the silicon nitride film and the less likely the coating is to absorb moisture, the less likely the coating is to peel off from the silicon nitride film.
[0147] A: Even after exposure to the above atmosphere for 96 hours, 50% or more of the area of the coating film was in close contact with the silicon nitride film.
[0148] B: Even after exposure to the above atmosphere for 48 hours, 50% or more of the area of the coating film was not peeled off from the silicon nitride film, but after exposure for 96 hours, 50% or more of the area of the coating film was peeled off from the silicon nitride film.
[0149] C: Even after exposure to the above atmosphere for 24 hours, 50% or more of the area of the coating film was not peeled off from the silicon nitride film, but after exposure for 48 hours, 50% or more of the area of the coating film was peeled off from the silicon nitride film.
[0150] D: After exposure to the above atmosphere for 24 hours, 50% or more of the area of the coating film is peeled off from the silicon nitride film.
[0151] (3) Volatility
[0152] The composition was left to stand in an argon atmosphere at 20°C (dew point temperature -70°C) for 24 hours. The weight loss ratio of the composition thus produced was measured. The case where the weight loss was 0.5% or less was evaluated as "A", the case where it was 0.5 to 1% was evaluated as "B", and the case where it was 1% or more was evaluated as "C".
[0153] (4) Viscosity
[0154] A rheometer (Anton Paar Japan, Model DHR-2) was used at a temperature of 25°C and a shear rate of 1000 s. -1 The viscosity of the composition was measured under the conditions of .
[0155] (5) Inkjet properties
[0156] The composition was placed in a process box of an inkjet printer (manufactured by Ricoh, model MH2420), and after confirming that the composition in the process box could be discharged from the nozzle of the inkjet printer, the composition was discharged from the nozzle to continuously print a test pattern. As a result, the case where the composition could be discharged for 1 hour and the discharge action was stable was evaluated as "A", the case where the composition could be discharged for 1 hour but the discharge action was intermittent and unstable was evaluated as "B", and the case where the nozzle was clogged and the composition could not be discharged before 1 hour from the start of discharge was evaluated as "C".
[0157] (6) Glass transition temperature
[0158] The composition was applied to form a coating film, and the coating film was irradiated with an LED-UV irradiator (peak wavelength 365 nm) manufactured by Panasonic Electric Works Co., Ltd. at a temperature of about 50 mW / cm 2 A film having a thickness of 200 μm was prepared in 30 seconds under the condition of . The glass transition temperature of a sample cut out from the film was measured using a viscoelasticity measuring apparatus (manufactured by Hitachi High-Tech Science Co., Ltd., model DMA7100).
[0159] (7) Gas release evaluation
[0160] The gas released when the cured product of the composition was heated was sampled by the headspace method and measured by gas chromatography. 100 mg of the composition was placed in a headspace vial and the composition was irradiated with an LED-UV irradiator (peak wavelength 365 nm) manufactured by Panasonic Electric Works Co., Ltd. at a cumulative light intensity of 1500 mJ / cm 2After curing the composition by irradiating ultraviolet rays under the conditions of , the vial was sealed and heated at 80°C for 30 minutes, and the gas phase in the vial was introduced into a gas chromatograph for analysis. As a result, the case where the generated gas was 300 ppm or less was evaluated as "A", the case where it exceeded 300 ppm and was less than 500 ppm was evaluated as "B", and the case where it was 500 ppm or more was evaluated as "C".
[0161] [Table 1]
[0162]
[0163] [Table 2]
[0164]
Claims
1. A UV-curable resin composition for sealing an organic EL element, comprising an acrylic compound A and a photopolymerization initiator B, The acrylic compound A contains an acrylic compound A1 having a structure represented by the following formula (1) and a boiling point of 270° C. or higher. CH2=CR 1 -COO-(R 3 -O) n -CO-CR 2 =CH2 …(1) In formula (1), R 1 and R 2 are hydrogen or methyl, n is an integer greater than 1, R 3 is an alkylene group having 3 or more carbon atoms. When n is 2 or more, a plurality of R 3 are optionally the same as or different from each other, The acrylic compound A1 contains R 3 is a compound in which the alkylene group has 3 or more and 4 or less carbon atoms, The percentage of the acrylic compound A1 relative to the acrylic compound A is 50% by mass or more, The acrylic compound A does not contain a compound having a boiling point of 260° C. or less, or the proportion of the compound having a boiling point of 260° C. or less in the acrylic compound A is 10% by mass or less.
2. The ultraviolet curable resin composition according to claim 1, wherein The viscosity of the acrylic compound A1 at 25° C. is 25 mPa·s or less. 3 . The ultraviolet curable resin composition according to claim 1 , which is molded by an inkjet method.
4. The ultraviolet curable resin composition according to claim 1 or 2, wherein The acrylic compound A further includes a compound A21 having three or more (meth)acryloyl groups in one molecule. 5 . The ultraviolet curable resin composition according to claim 1 , wherein the glass transition temperature of the cured product thereof is 80° C. or higher.
6. The ultraviolet curable resin composition according to claim 1 or 2, wherein The acrylic compound A further contains at least one compound selected from the group consisting of a compound A41 having silicon in its molecular skeleton, a compound A42 having phosphorus in its molecular skeleton, and a compound A43 having nitrogen in its molecular skeleton.
7. The ultraviolet curable resin composition according to claim 1 or 2, wherein The percentage of components having a boiling point of 270° C. or higher in the acrylic compound A is 80% by mass or more.
8. A method for manufacturing an organic EL light-emitting device, comprising: manufacturing an organic EL light-emitting device comprising an organic EL element and a sealing material covering the organic EL element; The method for producing an organic EL light-emitting device comprises forming the ultraviolet curable resin composition according to any one of claims 1 to 7 by an inkjet method, and then irradiating the ultraviolet curable resin composition with ultraviolet rays to cure the composition, thereby producing the sealing material.
9. The method for manufacturing an organic EL light-emitting device according to claim 8, wherein: After the ultraviolet curable resin composition is heated, the ultraviolet curable resin composition is molded by an inkjet method. 10 . An organic EL light-emitting device comprising an organic EL element and a sealing material covering the organic EL element, wherein the sealing material is a cured product of the ultraviolet curable resin composition according to claim 1 .
Citation Information
Patent Citations
Method of manufacturing fine zeolite
JP2013049602A
Production process for nano-zeolite
JP2016069266A
Acrylic resin for adhesive and acrylic resin composition for adhesive comprising the same
JP2016216592A
Ultraviolet-curable resin composition, method of manufacturing organic el light-emitting device, and organic el light-emitting device
JP2018145430A
Radiation-curable composition containing hydrophilic nanoparticles
JP2018510449A